IDEOLOGICAL FOUNDATIONS OF THE STUDY OF ECONOMIC SCIENCE - Namazova Nodira Djumaevna (Bright Mind Publishing, 2025)
The article explores the ideological foundations that underpin the study of economic science, emphasizing the interplay between economic theories and the broader philosophical, political, and cultural contexts in which they emerge. It examines how different ideological paradigms—such as liberalism, socialism, conservatism, and neoliberalism—have shaped the formulation, interpretation, and application of economic principles. The paper also discusses the epistemological assumptions underlying economic models and their implications for economic policy and education. Special attention is given to the ways in which ideological biases can influence economic discourse, shaping the priorities and values embedded in economic research and teaching. The study concludes that recognizing and critically analyzing these ideological foundations is essential for developing a more reflective and inclusive economic science that responds to the complex realities of contemporary societies.
Keywords: Economic science, ideology, economic theory, liberalism, socialism, neoliberalism, epistemology, economic policy, economic education, critical analysis.